Religious Value in the Drama Script “Those Who Always Follow You” by Teater Adab - Wardani, Intan Kusuma; Sujarwoko, Sujarwoko; Sardjono, Sardjono; Lailiyah, Nur (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Diverse societies have different religious beliefs; of course, there will be many points of view regarding religion. Therefore, the religious value in the drama script can be used as a reference from different points of view from each religious belief. This study aims to analyze the religious values contained in the drama script, as these values can be applied in everyday life. Religious values are divided into three: human relationships with God, humans with humans, and humans with the universe. This research focuses on the religious value of human relationships with God and humans with the universe, namely the supernatural. Based on this, the problem formulations contained in this study are as follows: How is the religious value in the play “Those Who Always Follow You” by Teater Adab? This research method uses a descriptive qualitative method. Data collection techniques in this research are reading, listening and recording techniques.  Based on the conclusion, the results of this study are recommended: 1). The study of the play further observes the religious value. 2). In education, it can be used to observe structural aspects as a learning process.